1999
DOI: 10.1046/j.1365-2168.1999.01185.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of anatomical resection and des-γ-carboxy prothrombin in patients with hepatocellular carcinoma

Abstract: Anatomical resection appeared to have a beneficial effect on recurrence-free survival after hepatectomy for HCC. DCP measurement was effective in predicting HCC recurrence and had the advantage that it can be assessed before operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
174
2
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(185 citation statements)
references
References 32 publications
6
174
2
3
Order By: Relevance
“…These results are in accordance with previous reports [3,8,10,12,[15][16][17][18][19][34][35][36] . However, limiting this to small hepatocellular carcinoma, DCP alone is the independent prognostic factor for both tumor recurrence and patients' survival, while presence of microscopic vascular invasion is a prognostic factor in patients outside the criteria.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These results are in accordance with previous reports [3,8,10,12,[15][16][17][18][19][34][35][36] . However, limiting this to small hepatocellular carcinoma, DCP alone is the independent prognostic factor for both tumor recurrence and patients' survival, while presence of microscopic vascular invasion is a prognostic factor in patients outside the criteria.…”
Section: Discussionsupporting
confidence: 83%
“…Many reports state high DCP levels to be of poor prognostic value. It has been shown that patients with high DCP and high AFP levels show poor prognostic factors [4,6,[10][11][12][14][15][16][17][18] . Thus, a prognostic staging system in which DCP has been incorporated is being suggested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DCP, also known as prothrombin induced by vitamin K absence-II (PIVKA-II), is an abnormal prothrombin protein that is present at higher levels in the serum of HCC patients. Since the report by Liebman et al [18], DCP has been recognized as not only a highly specific marker for HCC but also a predictor of prognosis of HCC patients [86,87]. AFP-L3 is a fucosylated variant of AFP that reacts with Lens culinaris agglutinin A and can differentiate an increase of AFP due to HCC from that due to benign liver disease [20,21,82].…”
Section: Discussionmentioning
confidence: 99%
“…Since the report by Liebman et al [171], DCP has been recognized as not only a highly specific marker for HCC but also a predictor of prognosis of HCC patients [172,173]. According to the systematic review, the sensitivity, specificity, and LR?…”
Section: Des-c-carboxyprothrombinmentioning
confidence: 99%